Land use changes in Southeastern Wisconsin: The landscape pattern project - (:unkn) unknown (My University, 1980)
Since settlement began in the 1830's, the native forest, wetland and prairie vegetation has been replaced by pasture, cultivated fields, highways, towns and cities. Fragmentation of the forest into smaller and smaller isolated patches influences the biological diversity of the remaining patches, as well as species replacement patterns and dispersal of seed and other propagules. This drastically alters the integrity of the regional system. This study documents changes in patterns of land use and forest vegetation and investigates factors influencing these changes and the effect of the present pattern on ecosystem maintenance. This work is part of a larger study examining many areas throughout the Deciduous Forest biome.
Keywords: forest history; land use; fragmentation